Nanosheet like CaO/C derived from Ca-BTC for biodiesel production assisted with microwave. (15th November 2022) - Li, Hui; Wang, Yongbo; Han, Zhihao; Wang, Tianyu; Wang, Yunpu; Liu, Chenhui; Guo, Min; Li, Guoning; Lu, Wanpeng; Yu, Mingzhi; Ma, Xiaoling
Graphical abstract: Highlights: Nanosheet like structure CaO/C is constructed from Ca-BTC. CaO is tightly anchored in carbon nanosheet and possesses ultrahigh surface area. Ca-800N owns strong microwave absorbing capacity with ε'' of 3.64 F/m. Ca-800N exhibits highly stable catalytic activity in transesterification with microwave. Abstract: Calcium oxide (CaO) is recognized as an efficient heterogeneous catalyst for biodiesel production. Nevertheless, the stability of CaO has always been a great challenge. This study creatively designs a highly stable CaO catalyst with strong microwave absorbing capacity, of which CaO is anchored in nanosheet carbon. For this purpose, Ca-BTC (Benzenetricarboxylic acid, BTC) is initially synthesized and calcined in nitrogen atmosphere, the obtained catalyst is characterized by TG, XRD, TEM, EDS, SEM, XPS, FTIR, Hammett indicator, N2 absorption/desorption, and the dielectric property is also evaluated. Results indicated the prepared Ca-800N achieves the maximum conversion of 97.37% with catalyst amount of 8 wt% and molar ratio of methanol/oil of 9:1 at 60 °C within 30 min in 400 W microwave field, the conversion of 94.01% is still achieved after being used six cycles. Furthermore, dielectric constant and dielectric dissipation factor of Ca-800N is measured as 33.11 F/m and 3.64 F/m.